Awareness of Crowdfunding Platforms in Bengaluru City : An Empirical Study - Meghana, C.; Cariappa, Punith (Indian Journal of Research in Capital Markets, 2020)
Crowdfunding is a solicitation of funds (generally in small amounts) from multiple investors through a web-based platform or social networking site for a specific project, business venture, or social cause. The concept of awareness, acceptability, and evaluation plays a significant role, reaching more members and the success of campaigns that can benefit society at large. As awareness of crowdfunding among Indians is quite less as compared to developed countries with this background, the present study examined the awareness level of crowdfunding in Bengaluru city and also investigated whether there is an association between gender and awareness of crowdfunding. To accomplish the objectives, the data were collected using non – probability convenience sampling technique using Google Forms from 103 respondents and data were analyzed using suitable statistical techniques using percentage analysis and chi-square test.